Linear mode conversion of terahertz radiation into terahertz surface magnetoplasmons on a rippled surface of magnetized n-InSb - Kumar P.; Kumar M.; Tripathi V.K. (My University, 2025)
A new mechanics of linear mode conversion of terahertz (THz) radiation into THz surface magnetoplasmons on a rippled surface of magnetized n-InSb is proposed. The normally incident THz radiation, polarized in the direction of a ripple wave vector, imparts oscillatory velocity to electrons in the ripple layer. This velocity beats with surface ripple to produce a nonlinear current that resonantly drives the THz surface magnetoplasmons. In the presence of an applied magnetic field, the surface plasmon (SP) mode splits into two modes - an upper mode and a lower mode. The amplitude of the SP for the upper branch mode is higher than that for the lower mode. © 2016 Optical Society of America.